Orchestration of distributed hetero-geneous sensor networks and Internet of Things - Wilusz, Daniel; Rykowski, Jarogniew (Business Informatics, 2014)
This paper focuses on management of sensor networks and Internet of Things. Two alternative architectures for service management in IoT and sensor networks are analyzed. The first one is based on Open Service Gateway (OSGi) framework and Remote Services for OSGi (R-OSGi) bundle. The second one extends Representational State Transfer (REST) paradigm. The analysis confirms that these two architectures meet the requirements of both sensor networks and IoT management. However, to bypass the disadvantages of these architectures, the new one is proposed being a combination of the analyzed architectures. In our proposition, the OSGi framework is applied to manage local sensor networks and RESTbased architecture allows for managing complex services in Internet of Things. The RESTlet OSGi module integrates the OSGi management system for sensor networks with REST-based management of Internet of Things
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 114-129
Keywords: Internet of Things; internet rzeczy; Future Internet; sensor network; REST; OSGi; Internet Przyszłości; sieci sensorowe